An empirical kinetic approach to study the occurrence of ion exchange in the piperidinolysis of phenyl salicylate in the presence of cationic micelles and inert salts / Nor Saadah Mohd Yusof - Nor Saadah, Mohd Yusof (2011)
In this study, the ion-exchange constant, KX Br for the ion-exchange process X-/Brinvolving different halo-substituted organic salts, MX and CTABr micelle in aqueous system were determined by a semiempirical kinetic approach with the interest of investigating the relationship of the ion-exchange constant to the micellar aggregation behavior. The first chapter contains the reviews of literature studies on this area. Chapter 2 listed all the materials used as well as the experimental details for the study. It consists of 2 parts: (a) kinetic measurements which show the effect of [MX] on the rate of piperidinolysis of phenyl salicylate in the absence and presence of CTABr; and (b) the rheological investigation. In chapter 3, the results of the kinetic measurements and rheological behavior of the reaction mixtures are presented. The mean values of KX Br are 12.8 ± 0.9, 13.4 ± 0.6, 4.67 ± 0.7, 50.3 ± 2.0, 47.9 ± 2.5, 8.82 ± 0.3, 71.2 ± 5.6, 62.1 ± 5.2, 11.2 ± 0.9 and 144 ± 12 for MX = 3- and 4-FC6H4CO2Na; 2-, 3- and 4-ClC6H4CO2Na; 2-, 3- and 4-BrC6H4CO2Na; and 2- and 4-IC6H4CO2Na, respectively. Shear thinning behavior of the plots of shear viscosity versus shear rate at constant [MX] and [CTABr]T are observed in all systems except when MX = 2-ClC6H4CO2Na for which the value of KX Br is the lowest. In Chapter 4, detailed discussions of the results are given. The values of KX Br offer quantitative evidence of the perception that the strong micellar binding of certain counterions is the cause of the micellar structural transition from spherical to cylindrical to wormlike entangled micelles. Viscosity maxima of the plots of shear viscosity as a function of [MX] are known as the characteristic features of the wormlike micellar solution. Thus, it may be concluded that the magnitudes of the thermodynamic ion-exchange constant, KX Y for ion-exchange process X-/Y- on the cationic micellar surface in aqueous solution could affect the physical properties such as the structure of micelles of ionic surfactant solutions.